JURIDICAL ANALYSIS OF THE LEGAL FRAMEWORK ON SAFE COMMUTING PROVIDED BY COMPANIES FOR FEMALE WORKERS AT NIGHT - Uba Dawam Mubarok; Deni Yusup Permana (Hukum Responsif, 2026)
This research is motivated by the limited legal arrangements regarding companies' obligation to ensure safe commuting for women who work at night. Legally, Article 76 of Law Number 13 of 2003 concerning Manpower specifically regulates the provision for female workers. The main problem is the time limitation in Article 76 paragraph (4) of Law Number 13 of 2003 concerning Manpower, which only requires the provision of shuttle transportation at 23:00 – 05:00, thus creating a legal gap in practice. This study aims to analyze the legal framework governing the company's obligations to provide safe commuting and to examine the legal remedies available if these obligations are not met. The research method used is normative juridical, employing legislative, conceptual, and case approaches, and is analyzed descriptively and analytically. The results of the study show that regulations related to safe commuting already exist in principle but remain limited, leaving opportunities for companies to avoid legal obligations. In addition, legal remedies are more preventive and corrective, through internal company policies, labor supervision, and human rights approaches. The conclusions of this study show a gap between formal compliance and substantive protection for women workers. Therefore, it is recommended to review regulations, strengthen internal policies, and increase supervision to ensure optimal protection.